To Supplement or Not to Supplement: Are Inuit Getting Enough Vitamin D? - Frost, Peter (Études Inuit Studies, 2016)
Inuit have vitamin D blood levels that generally fall within the range of insufficiency, even when they live on a traditional diet of fish and game meat. Without this vitamin, bones soften and become deformed, a condition called rickets in children and osteomalacia in adults. Until recent times, however, this condition was much rarer among Inuit than among non-Inuit, even when the latter included people living near Inuit communities under similar conditions of climate and housing. This rarity was attributed to extended breastfeeding and a high-meat/low-cereal diet. The situation subsequently reversed, with Inuit becoming more at risk of developing rickets, first in Labrador during the 1920s and later elsewhere. To reduce this excess risk, researchers have recommended vitamin D supplementation, arguing that breast milk has too little vitamin D and that even a traditional diet cannot provide the recommended daily intake. We should ask, however, whether the problem is definitional. Inuit may have lower levels of vitamin D because they need less, having adapted culturally and physiologically to an environment where this vitamin is less easily synthesized in the skin. These adaptations include a diet that enhances calcium bioavailability (by means of β-casein in breast milk, certain unknown substances in meat, and absence of phytic acid), as well as genetic changes that enable vitamin D to be used more efficiently. Although Inuit are today more at risk of developing rickets than are non-Inuit, this excess risk is nonetheless small and seems to have a dietary cause—namely, early weaning and abandonment of a high-meat/low-cereal diet.